Pengaruh Mobile Banking, Ukuran Perusahaan, Struktur Modal dan Growth Opportunity terhadap Kinerja Keuangan Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia periode 2018-2022 - Fika Yuliastanti; Indrayeni (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research aims to determine the direct influence of mobile banking, company size, capital structure and growth opportunity on financial performance in the Banking Company Sector listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. The data used as samples in this research are annual reports and financial reports of banking companies listed on the IDX for the 2018-2022 period. The method used in this research is a quantitative method. The sampling used was a purposive sampling technique. The model used in this research is a regression model processed with the statistical data processing application SPSS version 21. The results of the research show that mobile banking has a significant effect on financial performance. Company size has a positive and significant effect on financial performance. Capital structure has no significant effect on financial performance and growth opportunity has no significant effect on financial performance. Simultaneous results of mobile banking, company size, capital structure and growth opportunity together have a significant effect on financial performance. The contribution of this research is expected to become a basis for banks in evaluating financial performance from efforts to utilize mobile banking, increasing the number of assets as an illustration of company size and banking companies can consider capital structure management and growth opportunities to improve the quality of financial performance in the future. Apart from that, it is a suggestion for the public to support bank performance through the use of banking products. As well as suggestions for the government and investors in making the right decisions.